KUALFIKASI TERSANGKA TINDAK PIDANA NARKOTIKA SEBAGAI PENYALAHGUNA ATAU PENGEDAR DENGAN MENGGUNAKAN BARANG BUKTI BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Mene, Meydianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: In Law Number 35 of 2009 concerning Narcotics, the use of evidence to determine a suspect's qualifications as a narcotics dealer, owner or abuser does not specifically regulate these qualifications, which has an impact on the use of articles that are suspected of not being given to the perpetrator. This multi-interpretation article means that perpetrators of narcotics crimes (dealers) will take refuge as if they were victims of narcotics crimes. This will have an impact on the imposition of sentences with short sentences, thereby causing injustice in the implementation process. The application of different criminal penalties is very detrimental and does not reflect a sense of justice because a narcotics user before using narcotics is guaranteed to have to own or buy it first and when narcotics have been purchased or owned before being used they have been arrested by the police or BNN so that automatically the results of the laboratory examination of the urine in question will be negative.Keywords: Evidence, Narcotics, Dealers, Narcotics Abusers.